Social media usage among users of Sabah state library, Malaysia - Awang Ali, Siti Rinawaty; Wan Mokhtar, Wan Nor Haliza; Hussin, Norhayati (Faculty of Information Management, 2025)
The evolution of Information Technology and the rise of the digital era since the year 2000 has been a challenging mission for libraries all over the world to be still relevant in providing information in all kinds of practices. Since the year 2020, the social media platform has grown rapidly and it has been the most visited site on the internet. Sabah State Library as a responsible library for all the districts in Sabah, Malaysia, needs to take the challenge in order to remain relevant in this field. Therefore, librarians, library staff and the users need to be supportive and cooperative in implementing this new trends to achieve an impactful consequence as anticipated. The outcome of the study on the social media usage among users of the Sabah State Library, Malaysia are discussed in this paper.